PENGARUH LINGKUNGAN KERJA DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI KANTOR KECAMATAN WALANTAKA KOTA SERANG - Leny Afrianty; Suflani Suflani; Bambang Setyo Panulisan (Universitas Bina Bangsa, 2021)
The Walantaka District Office is one of the sub-districts in the city of Serang. Quality human resources are very important to achieve the goal. In addition, the work environment and motivation are important for agencies to achieve organizational goals. The purpose of this study was to determine the effect of work environment and motivation on employee performance. This type of research uses quantitative. The population of Walantak sub-district employees. The sample used is the saturated sample technique. The sample in this study were all employees of the Walantaka sub-district totaling 30 people. Data processing using SPSS 26 software. Hypothesis testing was carried out by descriptive statistical tests, validity and reliability tests, classical assumption tests, multiple linear regression tests, correlation coefficient analysis, coefficient of determination analysis and statistical hypothesis testing T test and F test. The results obtained from this study that the work environment affects employee performance while motivation does not affect employee performance, and simultaneously work environment and motivation affect employee performance